The mobile application Elsa as a self-learning tool to reinforce oral skills for young learners - Bonilla Quinde, Sonnia Jamilex (2023)
The main objective of this research is to analyze the benefits of the mobile application "ELSA" as a self-learning tool to reinforce oral skills for young students; in which qualitative analysis was applied, and interviews were conducted with the target group that had the purpose of identifying the incidences that have occurred in the educational institution regarding the speech and pronunciation of students. This research project has developed several theoretical and practical aspects related to the importance of pronouncing the English language correctly to develop communication skills more easily. It is anticipated that students will decrease any margins of error they may have and that new strategies will be provided to help students learn more about the English language's phonetics so they can express and understand their thoughts, feelings, and experiences. Through this research, the "Elsa" application is expected to be used as a self-learning tool to develop, reinforce, and improve the deficiencies in the oral skills of students from 8th to 9th grade of higher basic education at the Academia Naval Capitan Leonardo Abad Astudillo.